Comparison of Different Nutritional and Lifestyle Factors between Glaucoma Patients and an Age-Matched Normal Population - Waibel, Sören; Thomaschewski, Gregor; Herber, Robert; Pillunat, Lutz E.; Pillunat, Karin R. (Klinische Monatsblätter für Augenheilkunde, 2021)
Purpose To compare nutritional and lifestyle factors between glaucoma patients and an age-matched control group.Methods One hundred and ninety (190) glaucoma patients were enrolled in this study. The control group comprised 97 age-matched participants. Data on physical activity, nicotine smoking, and several nutritional habits like coffee and alcohol consumption as well as high-salt and high-protein intake were collected using a standardised questionnaire.Results Age and gender were not statistically significantly different between the groups. There was a tendency for higher physical activity in the glaucoma group in comparison to the control group (47.3 vs. 35.4%; p = 0.056). Statistically significantly more glaucoma patients were nonsmokers (n = 169; 89.4%) compared to the control group (n = 64; 66.7%; p = 0.001). Glaucoma patients were also more often teetotal compared to the control group (21.6% compared to 14.4%; p < 0.001). Similarly, more glaucoma patients drank larger amounts of coffee in comparison to the control group (p = 0.001). One hundred and seventy-six (96.7%) glaucoma patients and 88 (90.7%) control subjects had high-protein intake (p = 0.035). High-salt intake was significantly lower in the glaucoma group (69.3 vs. 73.2%; p = 0.018). Of the 190 glaucoma patients, 81 had early visual field impairments (MD > − 6 dB) and 109 patients had moderate (MD between − 6 dB and − 12 dB) to severe (MD < − 12 dB) visual field defects. The severity of visual field defects, whether early, moderate, or severe, had no statistically significant impact on lifestyle parameters.Conclusion Contrary to our original hypothesis that glaucoma patients would tend to follow an unhealthier lifestyle than the control group, the opposite was seen. Presumably, the cause of this healthier lifestyle is the desire to contribute positively through the course of the disease.
Keywords: open-angle glaucoma; lifestyle factors; physical activity; smoking; alcohol consumption; nutritional habits